2022
DOI: 10.1186/s41983-021-00437-7
|View full text |Cite
|
Sign up to set email alerts
|

The sociodemographic and clinical profile of children with an autism spectrum disorder in the oriental region of Morocco

Abstract: Background The objective of our study is to assess the clinical profile of autistic children in Morocco and the cultural perception of their parents. We collect data with a standard questionnaire on 130 children with autism spectrum disorder (ASD). They were recruited from child psychiatry consultation in the hospital for mental health from 2017 to 2019. This questionnaire assesses the socio-demographic characteristics of children and parents, personal and family medical history, the progress o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Regarding to the family income of the studied sample, present study shows that; more than half of the parents see that their income is exactly enough to their requirements. this is may be due to the spend a lot of to treat their children suffered from autism and because most of the mothers are house wife so that the family income exactly sufficient for the family's needs, this finding in agreement with Oneib et al, [32]who conducted a study among 130 children with autism and their parents followed in child psychiatry consultation of the hospital for the mental health for ASD for approximately 2 years, found that the family income and socioeconomic status of the family was mild or enough to the family needs.…”
Section: Kousha Et Al [22]supporting
confidence: 86%
See 1 more Smart Citation
“…Regarding to the family income of the studied sample, present study shows that; more than half of the parents see that their income is exactly enough to their requirements. this is may be due to the spend a lot of to treat their children suffered from autism and because most of the mothers are house wife so that the family income exactly sufficient for the family's needs, this finding in agreement with Oneib et al, [32]who conducted a study among 130 children with autism and their parents followed in child psychiatry consultation of the hospital for the mental health for ASD for approximately 2 years, found that the family income and socioeconomic status of the family was mild or enough to the family needs.…”
Section: Kousha Et Al [22]supporting
confidence: 86%
“…this result was disagree with Oneib et al, [32]who carried out a study on 130 parents of children having autism and found that the children with autism was co morbid with other organic and mental illness.…”
Section: Kousha Et Al [22]mentioning
confidence: 70%
“…Particularly in emerging countries such as Morocco, data on ASD children remain scarce [3,10,[20][21][22]. While there are available data on ASD obesity among young Moroccan children under the age of 12 residing abroad [23,24], the prevalence of ASD within Morocco itself remains elusive.…”
Section: Research Gap In Asd and Obesity In Moroccomentioning
confidence: 99%
“…Due to the established efficacy of RS and a desire to overcome the limitations of the traditional ABA intervention model, we conducted a first-of-its-kind pilot study evaluating the effectiveness of RS with treatment personalization capabilities. We used assessment records, sociodemographic data such as age and gender [ 33 , 34 ], and 6-month longitudinal treatment data from 29 ASD children.The paper is organized with a Literature review in Sect. 2 , followed by a Materials and methods in Sect.…”
Section: Introductionmentioning
confidence: 99%